WRASP: a new dimension of physical facility for teachers in education / Nurhidah Munawer ... [et al.] - Munawer, Nurhidah; Ahmad, Intan Zurina; Wan Omar, Wan Syazwani; Nor Mohamad, Ahmad Rizal (Universiti Teknologi MARA, Perak, 2020)
Dealing with whiteboards is a teacher's daily job despite the growth of technology. However, marker stains on the whiteboard from the previous lesson make the whiteboard become heavily stained and ghosting. Hence, WRaSp with three functions; write, erase and spray has been invented specifically to clean old marker stains or permanent markers on a whiteboard. It is also used to reduce the number of items carried by teachers to classes and ensure the cleanliness of the case from marker residue. A few prototypes have been created and trials have been done in KMPh itself. Number of sharing sessions had also been done with colleagues in KMPh and other agencies. WRaSp also has been highlighted in a few innovation competitions such as KKi'19, iTREX, InIIC series 2 and 3iDC. WRaSp has obtained its copyright and Industrial Design (ID) from Intellectual Property Corporation of Malaysia (MyIPO). We received positive feedback from various users including lecturers in KMPh and other agencies. 100% respondents agreed that WRaSp really facilitates TnL and expressed their willingness to use WRaSp. In a nutshell, being able to produce this innovation that can facilitate TnL sessions by creating a pleasant condition for both teachers and students is a huge success for us.